Multipaction Susceptibility Margins in Space Travelling wave Tubes - Chanakya, Talur; Manker, N. K.; Naidu, V. B.; Datta, S. K. (Defence Science Journal, 2021)
Study of multipaction breakdown margins in the output connector of a travelling-wave tube (TWT) is essential for application in satellite-borne systems. A TWT uses a coaxial ceramic window, a coaxial output coupler and / or a waveguide output coupler that are prone to multipaction breakdown boosted by high RF power due to the ion accumulation in critical regions during the transition of the satellite through plasma pockets in space. A detailed procedure for estimating the multipaction susceptibility margins in a TWT using CST studio and analytical equations is presented in this paper, and output couplers of two typical TWTs are analysed and the results are presented.